Regulation of Treg cells by cytokine signaling and co-stimulatory molecules - Zong, Yuan; Deng, Kaihang; Chong, Wai Po (Frontiers in Immunology, 2024)
CD4 + CD25 + Foxp3 + regulatory T cells (Tregs), a vital component of the immune system, are responsible for maintaining immune homeostasis and preventing excessive immune responses. This review explores the signaling pathways of the cytokines that regulate Treg cells, including transforming growth factor beta (TGF-β), interleukin (IL)-2, IL-10, and IL-35, which foster the differentiation and enhanc the immunosuppressive capabilities of Tregs. It also examines how, conversely, signals mediated by IL-6 and tumor necrosis factor -alpha (TNF-α) can undermine Treg suppressive functions or even drive their reprogramming into effector T cells. The B7 family comprises indispensable co-stimulators for T cell activation. Among its members, this review focuses on the capacity of CTLA-4 and PD-1 to regulate the differentiation, function, and survival of Tregs. As Tregs play an essential role in maintaining immune homeostasis, their dysfunction contributes to the pathogenesis of autoimmune diseases.This review delves into the potential of employing Treg-based immunotherapy for the treatment of autoimmune diseases, transplant rejection, and cancer. By shedding light on these topics, this article aims to enhance our understanding of the regulation of Tregs by cytokines and their therapeutic potential for various pathological conditions.